PEMASARAN JASA INFORMASI Dl PERPUSTAKAAN - Noorika Retno Widuri (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2000)
In general, marketing relates with distributing the real products such as products with have profit oriented. Marketing is important not only for business, but also for non-profit oriented institution or organization like library. Marketing in library does not distribute goods products but service products like information services for users. Library may optimize the services for users by doing some tricks in distributing information services. So, library will have better information types and kinde of works.Keyword: Library; Information services